The intensification of consecutive three tropical cyclones passing over a warm ocean eddy in the South China Sea - Luo, Xi; Yang, Wei; Yang, Lei; Wang, Dongxiao (Frontiers in Climate, 2022)
An extremely strong and long-lasting (more than eight months) oceanic warm core eddy existed in the South China Sea (SCS) during February-October in 2010. From July-August, 2010, three tropical cyclones (TCs; TC Conson, Chanthu and Mindulle) consecutively passed over this eddy and sustained at least 21 hours. The intensity change of all three TCs reached 20kt within 24 hours when they encountered with this eddy. In mid-late July, tropical cyclone heat potential (TCHP) is overall stronger in eddy region than in its surrounding region, thus TCHP plays an important role in the intensification of TC Conson and Chanthu. It is also found that the intraseasonal oscillation (ISO) and the quasi-biweekly oscillation (QBWO) can be important in favor of the further enhancement of TCs. The TCHP is too low to favor the intensity increase of TC Mindulle in late August, 2010, but weak vertical wind shear, ISO and QBWO act as key roles in the intensification of TC Mindulle.